2023
DOI: 10.3233/npm-221048
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of interventions to prevent intraventricular haemorrhage in premature infants: A systematic review and network meta-analysis

Abstract: BACKGROUND: Intraventricular haemorrhage (IVH) is a common problem in preterm infants, being a major cause of morbidity and mortality. Despite many randomised controlled trials comparing interventions to prevent IVH, the best prevention remains unclear. This study aims to review all the interventions which intended to reduce the incidence of IVH and compare them in a network meta-analysis. METHODS: A search on MEDLINE, EMBASE, Emcare, and CENTRAL was performed. Randomised controlled trials which evaluated neon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…Kalani et al [ 50 ] discovered that early ibuprofen administration had a similar IVH-preventive effect. Two recent meta-analyses revealed that indomethacin prophylaxis was associated with a lower rate of severe IVH [ 1 , 125 ]. In contrast, several retrospective studies and clinical trials reported that prophylactic indomethacin not only demonstrated no IVH-preventive effect but also increased the risks of impaired renal function and bleeding tendency [ 61 , 72 , 82 ].…”
Section: Postnatal Strategymentioning
confidence: 99%
“…Kalani et al [ 50 ] discovered that early ibuprofen administration had a similar IVH-preventive effect. Two recent meta-analyses revealed that indomethacin prophylaxis was associated with a lower rate of severe IVH [ 1 , 125 ]. In contrast, several retrospective studies and clinical trials reported that prophylactic indomethacin not only demonstrated no IVH-preventive effect but also increased the risks of impaired renal function and bleeding tendency [ 61 , 72 , 82 ].…”
Section: Postnatal Strategymentioning
confidence: 99%
“…IVH after preterm birth is a significant worldwide problem, and both IVH and PHVD are associated with significant increased mortality [ 5 ], and strongly influence decisions around limitation or withdrawal of care [ 6 ]. Reducing IVH and other perinatal brain injury is a key part of the UK National Maternity Ambition [ 7 ] and while a small number of interventions may reduce the risk [ 8 , 9 ], no effective treatment is currently available [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…These dynamics are critically modulated by “hemodynamically significant” changes in the degree of shunting of blood flow across the patent ductus arteriosus (PDA) ( 3 , 4 ). Adverse hemodynamic effects on IVH pathogenesis persist despite the common use of antenatal corticosteroids, delayed cord clamping, and indomethacin prophylaxis, which have each been shown to partly reduce the risk of IVH ( 5 ). Whether aggregate strategies that achieve greater hemodynamic stability in preterm infants by addressing specific physiologic targets can reduce the risk of severe IVH and other outcomes of prematurity has been uncertain.…”
mentioning
confidence: 99%